PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM STUDI PADA PERUSAHAAN JAKARTA ISLAMIC INDEX - Putri, Sherly Arnandia; Idayati, Farida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTFinancial statement has experienced a lot of changes in the last years. This research is required to be analyzed in order to evaluate the performance which has been achieved by the company management in the past and as the consideration in preparing the company plan in the future. This research is meant to analyze the influence of financial performance to the stock price at Jakarta Islamic Index which are listed in Indonesia Stock Exchange in 2011-2015 periods.This research has been carried out by using the secondary data which has been obtained from the financial statement in Indonesia Exchange (IDX). The sample collection technique has been done by using purposive sampling method and the samples are 19 companies, 95 data have been obtained as the observation data. There is multicollinearity assumption test in one of the variables i.e. Return on Equity (ROE) that should be eliminated because of the occurence of multicollinearity syndrom.The result of the research shows that current ratio (CR) does not give any influence to the stock price, return on asset (ROA) give influence to the stock price, earnings per share (EPS) give influence to the stock price, and debt to equity ratio (DER) does not give any influence to the stock price.Keywords: Current Ratio (CR), Return on Asset (ROA), Earnings per Share (EPS), Debt to Equity Ratio (DER), Stock Price.